Intrinsically flame retardant polyamides: Research progress in the last 15 years - Nikita Drigo; Sabyasachi Gaan (Advanced Industrial and Engineering Polymer Research, 2023)
Polyamides are essential thermoplastics whose current worldwide annual production exceeds 10 million tons. They are ubiquitous and easily ignitable polymeric materials that require addition of flame retardants to comply with fire safety requirements for various applications. Flame retardant additives can be incorporated into polymer matrix as fillers or at the molecular level, implying use of reactive additives. The latter approach is less developed, but usually offers several advantages over adding flame-retardant fillers: lower additive loading used to achieve specific level of fire performance, no flame-retardant migration with time, lower corrosiveness, better polymer stability etc. Rendering polyamides intrinsically flame retardant is therefore highly desirable. In this review we survey progress in inherently flame-resistant polyamides done over the period from 2004 to 2020. The polymers are grouped according to their chemical structures: aliphatic, semiaromatic and aromatic polyamides, polyamidoimides and hybrid siloxane-polyamides. Their monomer preparation, synthesis details, thermal properties and fire performance are discussed. The minimal inclusion criterion for this review was reported fire-resistance performance: either V-1/V-0 rating achieved in UL-94 burning tests or experimental or calculated LOI above 23%.